Achievements, Significance, and Limitations of Modern Poetry : नयी कविता की उपलब्धियाँ, महत्व एवं सीमाएं - Meena, Tulsi Ram (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
The uniqueness of modern poetry’s narrative poems can be observed in terms of their creative inspiration, stylistic composition, and philosophical outlook on life. Analyzing the fundamental consciousness and thematic departures of these narrative poems leads us to the conclusion that Andha Yug critiques the moral decline of a transitional society, Kanupriya captures the emotional intensity of devotion, Sanshay Ki Ek Raat and Pravad Parv serve as poetic allegories of guilt and repentance, Mahaprasthan blends mythological storytelling with modern awareness, Ek Kanth Vishpayi portrays humiliation and vengeance through a mythological framework, Atmajayi offers contemporary solutions to eternal philosophical questions, Shambuk integrates Dalit issues within historical narratives, Ila and Amitabh expresses philosophical reflections on historical love, and Ek Purush Aur presents a contemporary interpretation of historical events. Undoubtedly, the creative inspirations of these narrative poems are deeply connected to the evolving consciousness of the era and the high ideals of cultural values. Abstract in Hindi Language: नयी कविता के प्रबन्धकाव्यों का वैशिष्ट्य उनकी सृजन प्रेरणा, शिल्प विधान और जीवन दर्शन सम्बन्धी उपलब्धियों के संदर्भ में दृष्टव्य है। समीक्ष्य प्रबन्धकाव्यों की प्रवृत्तिमूलक चेतना के प्रस्थान बिन्दुओं का विश्लेषण करने पर हम सहज ही इस निष्कर्ष पर पहुँचते हैं कि ’अंधा युग’ संक्रान्तिकालीन समाज की मर्यादाहीनता पर प्रहार है, ’कनुप्रिया’ भावाकुल तन्मयता की प्रतिक्रियाओं का अंकन, ’संशय की एक रात’ और ’प्रवाद पर्व’-प्रायश्चित और परिताप के द्वन्द्व के काव्य रूपक, ’महाप्रस्थान’ -मिथकीय पुराख्ययान में आधुनिकता का बोध, ’एक कण्ठ विषपायी’-अपमान बोध एवं प्रतिशोध वृत्ति पर आधृत पौराणिक इतिवृत, ’आत्मजयी’ पुराख्यानक चिरन्तन प्रश्नों का युगीन समाधान, ’शम्बूक’-पुरावृत्त में दलित वर्गीय समस्याओं का समावेश ’इला और अमिताभ’-ऐतिहासिक प्रेम सम्बन्धों की दार्शनिक अभिव्यक्ति ’एक पुरूष और’-समकालीनता पर इतिवृत का आरोप है। निश्चय ही समीक्ष्य प्रबन्धकाव्यों की सृजनात्मक प्रेरणाओं के सूत्र युग जीवन के समुन्नत बोध ओर सांस्कृतिक उच्चादर्शो से जुड़े हुए हैं। Keywords: नयी कविता, सृजन प्रेरणा, शिल्प विधान और जीवन दर्शन, प्रबन्धकाव्यों।